A systematic review of fatigue behaviour of laser welding titanium alloys. (2021) - Paranthaman, V.; Dhinakaran, V.; Sai, M. Swapna; Devaraju, A.
Abstract: In the existence era, the usage and need for Titanium (Ti) alloys has been increased for manufacturing weight-less products of machine-made automobile and aerospace tools with increased application of multi-material design. When compared to conventional manufacturing techniques, titanium and its alloys are categorized through better machinability, enhanced melting of temperature, great strength-to-weight ratio, lower thermal conductivity, and increased reaction to oxygen. In recent years, numerous assemblage systems have been pondered to manufacture Ti alloys but Laser Beam Welding (LBW) opens a worthwhile possibility towards other techniques for joining of titanium and alloys in industries due to its adaptability, great and explicit heat input, tractability. In optimal process circumstances, however there occurs a problem such as poor elongation and resistance to corrosion joined with lower fatigue properties, the strength-to-weight ratio of laser welded titanium alloys found to be approaching to unique material. In this study, a small review on the fatigue behaviour of laser welding titanium alloys has been analysed to enhance its mechanical properties, influence of process parameters, fracture mechanisms.